Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1080/23802359.2021.1872427
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome sequence of Michelia balansae var. balansae (Aug. Candolle) Dandy, a timber and spices species in Magnoliaceae

Abstract: Michelia balansae var. balansae (Aug. Candolle) Dandy is a timber and spices species in Magnoliaceae, native to China and Vietnam. In this paper, the complete chloroplast genome (cpDNA) and basic annotated information were reported and its phylogenetic relationship with other species in Magnoliaceae was analyzed. The size of chloroplast genome of M. balansae var. balansae is 160,134 bp, which exhibited a typical quadripartite struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The previous studies on M. balansae focused on pollen morphology and ultrastructure (Xu & Kirchoff, 2008), propagation (Nguyen et al, 2012), influence of leaf extract on the activity of cholinesterase from pig serum (Chen et al, 2013), distribution survey and conservation situation evaluation (Nguyen et al, 2015), conservation carrying out (Nguyen, 2016), and the complete chloroplast genome sequence (Sima et al, 2021). A study on the chemical compositions of flower essential oil of M. balansae in China indicated that essential oil consisted of two main constituents: ethyl hexanoate (61.0%) and limonene (15.7%) (Zhu, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies on M. balansae focused on pollen morphology and ultrastructure (Xu & Kirchoff, 2008), propagation (Nguyen et al, 2012), influence of leaf extract on the activity of cholinesterase from pig serum (Chen et al, 2013), distribution survey and conservation situation evaluation (Nguyen et al, 2015), conservation carrying out (Nguyen, 2016), and the complete chloroplast genome sequence (Sima et al, 2021). A study on the chemical compositions of flower essential oil of M. balansae in China indicated that essential oil consisted of two main constituents: ethyl hexanoate (61.0%) and limonene (15.7%) (Zhu, 1993).…”
Section: Introductionmentioning
confidence: 99%
“… 2020 ; Sima et al. 2021 ) for ML analysis was based on the TVM + F+R2 model (Kalyaanamoorthy et al. 2017 ), using 1000 bootstrap replicates (Gao et al.…”
mentioning
confidence: 99%